Analisis Implementasi Kebijakan Program Makan Bergizi Gratis Di UPT SMP Negeri 6 Medan Kelas IX Tahun 2025 - Yuli Indriani Lubis; Julia Ivanna; Liber Siagian; Prayetno; Windawati Pinem (Jurnal Administrasi Politik dan Sosial, 2026)
This study aims to describe the implementation of the Free Nutritious Meal Program (MBG) policy at the UPT SMP Negeri 6 Medan for Grade IX in 2025 and identify supporting and inhibiting factors in its implementation based on aspects of communication, resources, disposition, and bureaucratic structure. The research is motivated by the implementation of the program that has been running, but has not been optimal in achieving policy objectives, especially in shaping students' nutritional awareness and behavior. This study uses a qualitative approach with descriptive methods. Informants were determined through purposive sampling techniques, consisting of the principal, implementing teachers, program coordinators, and grade IX students. Data collection techniques were carried out through interviews, observations, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldana. The results of the study indicate that the implementation of the MBG Program has been running administratively and technically, but has not been fully optimal. Communication between implementers is running quite well, but educational communication to students is still not optimal. The availability of resources is quite supportive, although its utilization is not optimal, including limited facilities such as cutlery. From the disposition aspect, implementers show commitment, but student participation and discipline are still low. The bureaucratic structure is in place, but it is not yet supported by standardized SOPs. Furthermore, there has been an expansion of beneficiary coverage to teachers as a means of adjusting implementation. The main inhibiting factors include a lack of nutrition education and suboptimal student behavior. Therefore, improvements are needed through strengthening educational communication, optimizing resources, and fostering student behavior to more effectively achieve program objectives.